Short Communication: The presence of Bull shark Carcharhinus leucas (Elasmobranchii: Carcharhinidae) in the fresh waters of Sumatra, Indonesia - VERYL HASAN; Maheno Widodo (Society for Indonesian Biodiversity, 2020)
Abstract. Hasan V, Widodo MS. 2020. Short Communication: The presence of Bull shark Carcharhinus leucas (Elasmobranchii: Carcharhinidae) in the fresh waters of Sumatra, Indonesia. Biodiversitas 21: 4433-4439. A single subadult specimen of Bull shark Carcharhinus leucas was photographed and captured by local fisherman using casting net on June 2020 in the upper Indragiri River, Riau Province, Indonesia. Carcharhinus leucas are one of only a few species of elasmobranchs that live in both marine and freshwater environments. This species currently listed as a near-threatened species based on the IUCN Red List Status. Singel specimen identified as C. leucas by the coloration of fresh specimen: white belly and greyish back, first dorsal fin high, tip of second dorsal and caudal fins black. Meristic characters measurement results as follows: total length 102 cm; fork length 86.3 cm; preanal length 65.1 cm; pre pelvic length 51.9 cm; pre pectoral length 22.5 cm; pre-orbital length 8.3 cm; head length 25 cm; pre-first dorsal length 29.4 cm; pre-second dorsal length 56 cm, and pre-caudal length 78.1 cm. This photo is considered as the third record from freshwaters of Sumatra after in the Batang Hari River, Jambi Province in 1997, and in the Musi River, South Sumatra Province in 2019. The photographic records indicate that a single specimen of C. leucas was found in the upper Indragiri River recorded more than 150 km inland. These results enhanced the understanding of C. leucas distribution in Sumatra freshwaters. Monitoring is needed to assess the possibility of the importance of the upper Indragiri River as a migration route, nursery, and growth ground of C. leucas. Studying small scale habitat use of C. leucas is challenged by their preferred habitats in freshwaters environments with fast-changing environmental conditions. Water conditions in the upper Indragiri River, namely salinity 0‰, temperature 25-27°C, dissolved oxygen 3.9-11.1 mg/l, are ideal for A. leucas habitat.